Analisis Kinerja, Seleksi dan Pengembangan Vendor Trucking di Perusahaan Logistik - Wati, Merlin Dyah; Praharsi, Yugowati; Sari, Devina Puspita (Prodi Teknik Industri, Fakultas Teknik - Universitas Katolik Indonesia Atma Jaya, 2020)
Freight forwarding is a logistics company which provide land delivery services rely heavily on trucking vendors. The available trucking vendors may not fulfill the company's expectations. Therefore the research was conducted to analyze the performance, selection process, management and development of 26 trucking vendors. The research began with the formation of a Critical Success Factor (CSF) and its development, namely a Key Performance Indicator (KPI) in accordance with company objectives. Then the CSF and KPI was weighted through the Analytic Hierarchy Process (AHP) method, determined the optimal performance value of each KPI, measured the performance of each vendor through the scoring method, analyzed the performance of the trucking vendor that was not optimal through Root Cause Analysis (RCA) by looking for the cause based on fishbone diagrams and FMEA tables, as well as providing suggestions regarding the management and development of trucking vendors. The results of the study were 11 CSFs and 28 KPIs that were formed. Based on the selection process conducted on 26 trucking vendors, there are 3 excellent vendors, 4 very good vendors, 11 good vendors, 3 matching vendors, and 5 unsatisfactory vendors. Furthermore, researcher conducted root cause analysis (RCA) of vendor representatives “matching” and “unsatisfactory” categories with fishbone diagrams and FMEA tables. Where the 5 highest RPN values from the FMEA table were given suggestions for improvement. Meanwhile, the excellent, very good, and good vendor categories are developed through strategic plans for the future.